Speech therapy for children with cleft lip and palate: Telepractice combined with face-to-face via Application for Articulation Therapy-Thai (AAT-T) in the pandemic of Covid-19 - Chanachai, Sasalaksamon; Prathanee, Benjamas (Journal of Associated Medical Sciences, 2025)
Background: In developing countries, access to speech therapy is restricted due to limited resources, lack of trained professionals, and geographical barriers. The COVID-19 pandemic further exacerbated these issues, making in-person therapy sessions difficult or impossible for many patients. In response, combining telepractice and mobile applications can help bridge this gap in accessibility to speech therapy services for children with cleft lip and palate. Objective: To compare the percentage of correct consonants (PCC) before and after implementing telepractice combined with face-to-face speech therapy using the Application for Articulation Therapy-Thai (AAT-T) for children with cleft lip and palate and to evaluate the effectiveness of implementing the combination of AAT-T with telepractice regarding improvement in pronunciation. Materials and methods: A one-group pretest-posttest design was employed to evaluate a cohort of 18 children aged 5 to 13 years who have undergone surgery for cleft lip and palate, including 12 boys and 6 girls. During pre- and post-implementation of telepractice and face-to-face speech therapy using the Application for Articulation Therapy-Thai (AAT-T), the percentage of correct consonants (PCC) for each individual was elicited via the Thai Connected Speech Standard Test by qualified speech and language pathologists. The speech therapy program consisted of five 45-minute face-to-face training sessions using AAT-T held once a month, along with 15 weekly telepractice sessions, each lasting 30 minutes, conducted over a period of five months. Results: After telepractice and face-to-face speech therapy with AAT-T, the numbers of PCC scores significantly increased (mean difference=8.64, SD=8.89; 95% confidence interval=4.22-13.06). Conclusion: Telepractice combined with face-to-face speech therapy using AAT-T effectively corrected the articulation disorders in patients with cleft lip and cleft palate. This strategy can be applied in any areas that have limited resources, geographical barriers, or a pandemic situation that requires social distancing in Thailand. The application can also be developed in any language for use in enhancing speech accessibility in other developing countries.